Early Roman Settlement under Grajski grič (Castle Hill) in Ljubljana. Gornji trg 3 - Vičič, Boris (Arheološki vestnik, 2002)
The material from the rescue excavations at Gornji Trg 3 in Ljubljana is presented in this article. The new discoveries elegantly supplement the previously known and published results about the settlement of the area under Grajski grič (Castle Hill) in the period of the formation of the colony of Emona and just before this. We investigated the remains of parts of wooden houses, destroyed by fire, that are dated to the last decade of the 1st century BC and the first decades of the 1st century AD. New elements in the material include a considerable quantity of metal artifacts (also of military significance), which were secondarily treated in many cases, which would indicate that the excavated structure had been a workshop (fabrica).